Olive Stone Delignification Toward Efficient Adsorption of Metal Ions - Gao, Ying; Aliques Tomas, Maria del Carmen; Garemark, Jonas; Sheng, Xia; Berglund, Lars; Li, Yuanyuan (Frontiers in Materials, 2021)
Olive stone is an important biomaterial waste product generated in large amount. As a lignocellulose material, olive stone could be a sustainable resource for biosorbents. In this work, olive stone powder delignification using NaClO2 was performed to enhance metal ion adsorption capacity. The influence of the treatment on olive stone powder physical-chemical properties was studied, including specific surface area, surface chemistry, morphology, etc. The white, delignified olive stone powder was investigated for metal ions (Fe3+, Cu2+, and Zn2+) removal and adsorption capacity. Olive stone delignification as a pre-treatment not only increases the accessibility of the olive stone powder but also broadens the applications to optical functions by the generation of a white powder.